Keragaman dan Distribusi Bakteri Patogen pada Ikan Mas (Cyprinus carpio) di Sentra Budidaya Ikan Mas Pabuaran, Subang, Jawa Barat - Andri Iskandar; Ahmad Justine Adillah; Muhammad Arif Mulya; Amalia Putri Firdausi; Mohamad Iqbal Kurniawinata; Wiyoto Wiyoto; Imam Tri Wahyudi; Dian Eka Ramadhani (Jurnal Ilmiah Samudra Akuatika, 2026)
The aquaculture sector frequently encounters disease problems, both infectious and non-infectious. Infectious diseases in fish can be caused by viruses, bacteria, parasites, and fungi, all of which can reduce productivity and threaten the sustainability of aquaculture operations. This study aimed to determine the distribution and types of pathogenic bacteria infecting common carp (Cyprinus carpio) and to analyze the prevalence of these pathogens in common carp farming centers located in Pabuaran and Salam Jaya Villages, Pabuaran District, Subang Regency, West Java. Sampling was conducted using a purposive sampling technique at four observation stations. Bacterial isolation was conducted from kidney and lesion tissues using Tryptic Soy Agar (TSA), followed by identification based on colony morphology, Gram reaction, and biochemical tests including catalase, oxidase, TSIA, MIO, O/F, and glucose fermentation tests. The results showed that in Pabuaran Village, Station 1 contained three types of pathogenic bacteria: Aeromonas sp. (87%), Pseudomonas sp. (6.7%), and Enterobacter sp. (6.7%), while Station 2 contained two types: Aeromonas sp. (93%) and Pseudomonas sp. (7%). In Salam Jaya Village, Station 1 contained Aeromonas sp. (87%) and Pseudomonas sp. (13%), while Station 2 contained Aeromonas sp. (87%) and Enterobacter sp. (13%). Overall, Aeromonas sp. was identified as the dominant pathogenic bacterium infecting common carp in both study locations.